Analisis Yuridis terhadap Modus Penghimpunan Dana Ilegal pada Investasi Forex FX Family dan Keterkaitannya dengan Tindak Pidana Pencucian Uang - Putri Nadia Niode; Hasnia Hasnia; Nur Fadilah Putri Yahya Boudelo; Siti Fadilah Rahmawati Ishak; Nurmila Lahamutu; Dea Putri Adawiyah Pelu; Moh. Taufik Panto; Dicky Firnanda (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2025)
Illegal investment schemes, often disguised as forex trading, have increasingly been used to deceive the public. The case of FX Family illustrates how unlicensed fundraising and misleading profit claims are combined with the diversion of funds into various personal and third-party accounts. This creates a predicate crime that can lead to money laundering. This study aims to examine how the FX Family scheme meets the criteria for illegal fundraising and how its transaction patterns constitute money laundering, specifically through the processes of placement, layering, and integration. The research utilises a normative juridical method that incorporates statutory, conceptual, and case study approaches. Legal sources include the Anti-Money Laundering Law, financial services regulations, investigative documents, and court decisions related to the FX Family case. The findings indicate that FX Family's operations fail to meet the criteria for lawful investment activity, demonstrating clear patterns of money laundering through fund transfers, asset purchases, and the concealment of transaction flows. The study recommends strengthening regulatory oversight, improving coordination among financial authorities, and enhancing public awareness to prevent similar schemes and reduce economic losses.